Current perspectives of ubiquitination and SUMOylation in abiotic stress tolerance in plants - Singh, Madhavi; Singh, Ananya; Yadav, Neelam; Yadav, Dinesh Kumar (Frontiers in Plant Science, 2022)
Post-translational modification (PTM) is a critical and rapid mechanism to regulate all the major cellular processes through the modification of diverse protein substrates. Substrate-specific covalent attachment of ubiquitin and Small Ubiquitin-Like Modifier (SUMO) with the target proteins, known as ubiquitination and SUMOylation, respectively, are crucial PTMs that regulate almost every process in the cell by modulating the stability and fidelity of the proteins. Ubiquitination and SUMOylation play a very significant role to provide tolerance to the plants in adverse environmental conditions by activating/deactivating the pre-existing proteins to a great extent. We reviewed the importance of ubiquitination and SUMOylation in plants, implicating its prospects in various abiotic stress regulations. An exhaustive study of molecular mechanisms of ubiquitination and SUMOylation of plant proteins and their role will contribute to the understanding of physiology underlying mitigation of the abiotic stresses and survival in plants. It will be helpful to strategize the improvement of crops for abiotic stress tolerance.